Coastal wave-energy attenuation by artificial wooden fences deployed for mangrove restoration: an experimental study - Shu, Anping; Zhu, Jiapin; Cui, Baoshan; Wang, Le; Zhang, Ziru; Pi, Chengling (Frontiers in Marine Science, 2023)
By offering natural protection along offshore wetlands, mangroves play a crucial role in providing great ecological and economic benefits to local communities. However, mangroves are currently facing an increasing threat of decline worldwide due to widespread human activities and climate change. Recently, eco-friendly wooden fences have been deployed along eroded coasts for mangrove restoration projects, and these fences have the capability to attenuate incoming waves and strengthen sediment deposition in new habitats for mangrove colonization and persistence. However, the design and performance of the fences used can differ substantially among different projects; therefore, it is necessary to study the major factors affecting the wave dissipation performance of these fences and find out a more effective structural design. Thus, we focus on two distinct types of fences with and without porous infill to study the function of infill porosity and frame density, and physical experiments of waves transmission through the fences were carried out in a wave flume, in which nine wooden fences with varied infill porosities (0.60–0.90) and frame densities (0.40 and 0.70) were predetermined to measure the wave transmission, reflection, and wave dissipation. In total, 180 experimental runs were conducted under 18 wave conditions with different wave steepness. The results showed that the fence with a lower infill porosity appears to increase wave transmission coefficient that comes at a cost of a higher reflection coefficient and less wave-energy dissipation inside the fence, and the fence with the highest porosity infills (90%) is nearly equivalent to the fence without any infills but a dense frame in terms of wave damping performance. Moreover, the wave transmission through both fences with and without infill can be remarkably affected by incoming wave steepness. The outcome of the research is not only indicating the importance of the appropriate infill porosity in attenuating incoming waves but also guiding the design of mangrove restoration project in offshore wetlands.